Insights from Intermittent Binocular Rivalry and EEG - Pitts, Michael A.; Britz, Juliane (Frontiers in Human Neuroscience, 2011)
Novel stimulation and analytical approaches employed in EEG studies of ambiguous figures have recently been applied to binocular rivalry. The combination of intermittent stimulus presentation and EEG source imaging has begun to shed new light on the neural underpinnings of binocular rivalry. Here, we review the basics of the intermittent paradigm and highlight methodological issues important for interpreting previous results and designing future experiments. We then outline current analytical approaches, including EEG microstates, event-related potentials, and statistically-based source estimation, and propose a spatio-temporal model that integrates findings from several studies. Finally, we discuss the advantages and limitations of using binocular rivalry as a tool to investigate the neural basis of perceptual awareness.